2012
DOI: 10.1016/j.virol.2011.10.006
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evolution of H5N1 avian influenza virus toward human-type receptor specificity

Abstract: Acquisition of α2-6 sialoside receptor specificity by α2-3 specific highly-pathogenic avian influenza viruses (H5N1) is thought to be a prerequisite for efficient transmission in humans. By in vitro selection for binding α2-6 sialosides, we identified four variant viruses with amino acid substitutions in the hemagglutinin (S227N, D187G, E190G, and Q196R) that revealed modestly increased α2-6 and minimally decreased α2-3 binding by glycan array analysis. However, a mutant virus combining Q196R with mutations fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
216
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 185 publications
(221 citation statements)
references
References 54 publications
4
216
0
1
Order By: Relevance
“…Although H5N1 mutants and reassortants have been shown to be transmissible in ferrets or guinea pigs (14,33,35,36), none of the naturally occurring H5N1 viruses is transmissible via respiratory droplet in these animal models. Certain H7N9 viruses are transmissible in ferrets (15,40), but their circulation so far is geographically restricted.…”
Section: Discussionmentioning
confidence: 98%
“…Although H5N1 mutants and reassortants have been shown to be transmissible in ferrets or guinea pigs (14,33,35,36), none of the naturally occurring H5N1 viruses is transmissible via respiratory droplet in these animal models. Certain H7N9 viruses are transmissible in ferrets (15,40), but their circulation so far is geographically restricted.…”
Section: Discussionmentioning
confidence: 98%
“…4 were isolated so that their HA genes could be sequenced and HA activation pH values measured. Bar charts for each of the four cages (5)(6)(7)(8) show the proportion of mutations with each residue at positions HA1-17 and HA2-106 over the course of infection. Proportions were determined by nextgeneration sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…Although these traits appear to be necessary for airborne transmissibility of influenza viruses, they do not appear to be sufficient. For example, H5N1 viruses engineered to have these traits were not airtransmissible among ferrets until a mutation increased HA thermostability and lowered the HA activation pH (6)(7)(8). The importance of HA stabilization in supporting the adaptation of influenza viruses to humans or enabling a human pandemic is not completely understood.…”
mentioning
confidence: 99%
“…It is known that in the human respiratory tract, NeuAc␣2,6-Gal is distributed on the upper respiratory tract and, in contrast, NeuAc␣2,3-Gal is found in the lower respiratory tract (20). It has been reported that the ␣2-3 SA-specific highly pathogenic avian influenza virus (H5N1) acquired increased affinity for human type receptors (␣2-6 SAs) by amino acid substitutions in hemagglutinin (HA) (21). This mutant H5N1 was shown to be transmissible only via direct contact in the ferret model (21).…”
Section: H Uman Enterovirus 68 (Ev68) (Species Human Enterovirus D;mentioning
confidence: 99%
“…It has been reported that the ␣2-3 SA-specific highly pathogenic avian influenza virus (H5N1) acquired increased affinity for human type receptors (␣2-6 SAs) by amino acid substitutions in hemagglutinin (HA) (21). This mutant H5N1 was shown to be transmissible only via direct contact in the ferret model (21). Moreover, the mutant H5N1 with affinity for human type receptors acquired transmissibility via respiratory droplets by introducing human N2 neuraminidase (NA) (21).…”
Section: H Uman Enterovirus 68 (Ev68) (Species Human Enterovirus D;mentioning
confidence: 99%